‘Just Play’ (JP) - creative arts therapies-based dyadic intervention for children with intellectual disability and their mothers: Study protocol for a mixed-methods randomized controlled trial - Rita Abramov; Amitai Stern; Rinat Feniger-Schaal; Cochavit Elefant; Limor Goldner; Tal-Chen Rabinowitch (PLoS ONE, 2026)
Background Play is a fundamental aspect of children’s development, fostering their cognitive, social, and emotional growth. However, children with intellectual disability (ID) experience limitations in their ability to engage in play, which can impact their relationships with caregivers. Parents of children with ID face heightened stress and reduced playfulness in their interactions with their children. Existing early interventions have primarily focused on behavioral parent training programs to manage challenging child behaviors, lacking a direct and positive approach to enhancing parent-child play interactions and relationships. Objective This study aims to develop, implement, and evaluate ‘Just Play’(JP), a creative arts therapies-based dyadic early intervention to enhance the quality of mother-child interactions through positive playful engagement. Methods A mixed-methods randomized controlled trial will be conducted with 60 mother-child dyads (children aged 3–7 with a prior ID diagnosis). Participants will be randomly assigned to either the JP dyadic intervention or to psycho-educational parent counseling control group. Quantitative data will include measures of emotional availability, mother and child playfulness, and the level of interpersonal synchrony between mothers and their children at baseline and post-intervention. Additionally, qualitative interviews with a subset of mothers in the JP group will be conducted at post-intervention and two-month follow-up to explore their experiences and identify the best practices of the intervention. Results & Implications This study will provide empirical evidence on the effectiveness of JP dyadic intervention in strengthening positive mother-child relationships in families of children with ID. Findings will inform future early intervention strategies, contributing to evidence-based guidelines for practitioners working with children with ID while emphasizing the unique contribution of creative arts therapies to this population. Trial registration ClinicalTrials.gov, registered August 6, 2024 ( NCT06541782 || https://clinicaltrials.gov/study/NCT06541782 ).